Antibody responses to the capsular polysaccharide of Neisseria meningitidis serogroup B in patients with meningococcal disease. - Granoff, D M (1995)
We measured antibody responses to meningococcal serogroup B (MenB) polysaccharide (PS) by enzyme-linked immunosorbent assay (ELISA) in sera from 94 patients from The Netherlands with disease caused by Neisseria meningitidis group B. The patients ranged in age from 3 to 73 years (mean age, 18.8 years). In initial studies we showed that the binding of a panel of MenB PS-reactive human immunoglobulin M (IgM) paraproteins to biotinylated MenB PS bound to avidin-coated microtiter wells was inhibited > 90% by the addition of soluble MenB PS or encapsulated group B meningococci. In contrast, inhibition of IgM anti-MenB PS antibody-binding activity in many of the patient sera was less than 50% (range, 20 to 94%). These data suggested a high frequency of nonspecific binding in the patient sera. Therefore, all serum samples were assayed in replicate in the presence or absence of soluble MenB PS, and only the inhibitable fraction of the binding signal was used to calculate the anti-MenB PS antibody concentrations. In 17 control patients with meningococcal disease caused by serogroup A or C strains, there was no significant difference in the respective IgM or IgG anti-MenB PS antibody concentrations in paired acute- and convalescent-phase sera. In contrast, in patients with MenB disease, the geometric mean IgM anti-MenB PS antibody concentration increased from 3.9 units/ml in acute-phase serum to 10.5 units/ml in convalescent-phase serum (P < 0.001). The corresponding geometric mean IgG anti-MenB PS antibody titers were 1:27 and 1:36 (P < 0.05). There was only a weak relationship between age and the magnitude of the logarithm of the antibody concentrations in convalescent-phase sera (for IgM, r2 = 0.06 and P < 0.05; for IgG, r2 = 0.08 and P < 0.01). Our data indicate that precautions are needed to avoid nonspecificity in measuring serum antibody responses to MenB PS by ELISA. Furthermore, although this PS is thought to be a poor immunogen, patients as young as 3 years of age recovering from MenB disease demonstrate both ImG and IgG antibody responses in serum.